2022
DOI: 10.1111/2041-210x.13875
|View full text |Cite
|
Sign up to set email alerts
|

Improving inferences and predictions of species environmental responses with occupancy data

Abstract: 1. Occupancy models represent a useful tool to estimate species distribution throughout the landscape. Among them, MacKenzie et al. 's model (2002, MC), is frequently used to infer species environmental responses. However, the assumption that detection probability is homogeneous or fully explained by covariates may limit its performance. Species should be more easily observed at sites with a higher number of individuals. We simulated data following occupancy model (RN) that accounts for abundance-driven hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Taylor's law: Giometto et al, 2015). Indeed, recent simulation-based studies have shown the Royle-Nichols model was more robust to overdispersion when zero-inflation was included, but, as was the case here, to remain identifiable studies should be designed to maximize detectability (Morán-López et al, 2022).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Taylor's law: Giometto et al, 2015). Indeed, recent simulation-based studies have shown the Royle-Nichols model was more robust to overdispersion when zero-inflation was included, but, as was the case here, to remain identifiable studies should be designed to maximize detectability (Morán-López et al, 2022).…”
Section: Discussionmentioning
confidence: 70%
“…Instead, introducing a zero‐inflation parameter to control for within‐stream spatial aggregation helped to resolve the estimation of detectability, and captured the within‐habitat heterogeneity that underpins observed patterns such as the rate of species accumulation (see Figure 2a) and past studies of mean–variance relationships (i.e., Taylor's law: Giometto et al, 2015). Indeed, recent simulation‐based studies have shown the Royle–Nichols model was more robust to overdispersion when zero‐inflation was included, but, as was the case here, to remain identifiable studies should be designed to maximize detectability (Morán‐López et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…HMSC is a type of joint species model and, as such, estimates responses to the environment for all species present in communities. However, in HMSC, species responses are not treated as a random term but explicitly modelled as a function of their traits and phylogeny (Morán‐López et al, 2022). Such an approach allows inferring the main ecological mechanisms behind species responses to the environment (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Here we use an HMSC occupancy model, based on the one recently developed by Mor an-L opez et al (2022), to assess individual bird species responses to rangeland management in the Rio de la Plata Grasslands (RPG). The RPG ecoregion is considered critically endangered and needs urgent attention (Hoekstra et al, 2005) due to the conversion of extensive areas of native grasslands into croplands and increased stocking rates that affect vegetation composition and structure (Modernel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%